Automated Regression Testing Procedure Based on ISO/IEC 29119 to Improve Software Testing Efficiency in a Software Development Environment - Galuh Oka Safitri; Leni Susanti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The growing complexity of modern software systems has increased the importance of effective software testing practices to ensure system reliability and quality throughout the development lifecycle. Among various testing activities, regression testing plays a crucial role in verifying that newly introduced changes do not negatively affect previously functioning system components (Yoo & Harman, 2012). However, in many organizations regression testing is still conducted manually, which can be time-consuming and may delay software release cycles. This study aims to design an automated regression testing procedure based on the ISO/IEC 29119 software testing standard in order to improve testing efficiency within a software development environment. A case study was conducted at PT. ABCD to examine the existing regression testing practices. Data were collected through semi-structured interviews with members of the Quality Assurance (QA) team, direct observation of testing activities, and analysis of testing documentation. The research process consisted of analyzing the current regression testing workflow, performing gap analysis with the ISO/IEC 29119 framework, and designing an automated regression testing procedure aligned with the standard. The study focused on five system modules comprising 420 regression test cases. The results indicate that manual regression testing required approximately eight working days to complete, with an average execution time of about nine minutes per test case. After implementing the proposed automated testing procedure, the execution time was reduced to approximately one day, or about 1.14 minutes per test case, resulting in an efficiency improvement of approximately 87.5%. These findings suggest that integrating automated regression testing with a structured testing framework such as ISO/IEC 29119 can significantly improve testing efficiency while also supporting better documentation, traceability, and process consistency. From a practical perspective, the proposed approach may help development teams accelerate testing cycles and support faster delivery of software updates in dynamic development environments.